Multi-Stage and Interregional Dynamics of Rice Price Transmission with Government Intervention: Evidence from Central Java and North Sumatra - Aprillia, Gita; Liu, Fangyi-; Syafrial; Baladina, Nur (HABITAT, 2026)
Purpose: This study aims to examine the multi-stage and interregional dynamics of rice price transmission in Indonesia by incorporating government intervention through BULOG rice prices. Specifically, it analyzes price linkages across the rice supply chain and compares Central Java and North Sumatra to identify regional differences in transmission patterns. Design/Methodology/Approach: This study employs monthly time-series data from 2019 to 2024, covering farmer-level harvested dry paddy prices, milling-level paddy prices, producer rice prices, BULOG consumer rice prices, and national rice prices. The analysis applies cointegration tests, Error Correction Model (ECM), Vector Autoregression (VAR), Granger causality, Impulse Response Function (IRF), and Forecast Error Variance Decomposition (FEVD) to capture long-run equilibrium, short-run dynamics, causal relationships, and shock transmission across market levels. Findings: The results indicate that rice price transmission differs across regions and supply chain stages. North Sumatra generally records higher producer and consumer rice prices, whereas Central Java exhibits greater upstream price volatility. Long-run equilibrium is found only between farmer-level and milling-level paddy prices, with adjustment speeds of 26.35% in Central Java and 25.19% in North Sumatra. Price transmission at subsequent stages is mainly short-term and dynamic. Government intervention through BULOG contributes to supply stabilization and price shock mitigation, but its influence on the overall price transmission mechanism remains limited. Originality/Value/Novelty: This study contributes to the literature by integrating a multi-stage supply chain framework, an interregional comparison, and government intervention through BULOG rice prices in a unified empirical model. The findings provide policy-relevant insights for designing more adaptive, region-specific, and market-integrated rice price stabilization strategies.